Algerian popular joke and the repercussions of globalization (مجلة إحالات, 2026)
The popular joke is a type of popular literature and a source for recording the heritage of peoples. Inits dimensions, it calls us to be optimistic through the method of laughter.The popular joke is a means of communication and entertainment, because it expresses the bitternessthat accompanies people's lives daily.But it has been exposed to the globalization revolution that has begun to shake its entity; this study attempts to understand the art of the popular joke while explaining how to confront the current ofglobalization so that there is no rupture between our generation and our ancestors.